Here come the nouns: Czech two-year-olds use verb number endings to predict sentence subjects - Smolík, Filip; Bláhová, Veronika (Cognition, 2022)
Two-year-old children can use gender or number agreement to predict upcoming words in phrases or sentences. However, most findings showed prediction from freestanding grammatical words, such as articles or copulas. While this shows knowledge of agreement relations, it might be limited to a narrow set of grammatical words. We examined the possibility that children at this age can use grammatical number agreement independently of specific closed-class words, testing whether they predict nouns from bound morphemes on lexical verbs. If this were the case, the emerging grammatical knowledge is unlikely to be lexically specific. Our first experiment replicated existing findings using number-marked copula, while the second experiment marked number on endings of four different verbs. Two-year-old children watched pairs of pictures showing single or multiple items while listening to sentences whose sentence-final subject referred to one of the two pictures. The grammatical Czech sentences contained a copula (Experiment 1: where is/are in the picture car/s?) or one of four number-marked lexical verbs (Experiment 2: Here jump/s the frog/s in the picture). Children in both experiments anticipated the subject from the verb or copula form. Children thus used number agreement predictively in the complex Czech copula system and lexical verbs marked by endings. This suggests that children understand grammatical number independently of specific grammatical words and supports the view that early knowledge of grammar is not lexically specific.
Keywords: lingvistika; Language; Česká republika; lidé; Linguistics; předškolní dítě; Czech Republic; jazyk (prostředek komunikace); Child, Preschool; Humans